The Influence of Problem-Based Learning Model Assisted by PhET Media on Critical Thinking Skills and Physics Learning Outcomes of High School Students - Nisrina Marliani; Aris Doyan; Muhammad Taufik (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to test the effect of problem-based learning model assisted by PhET media on critical thinking skills and physics learning outcomes of high school students. The type of research used is a Quasi experiment twith a pretest posttest control group design. The population in this study were all students of class XI of SMA Negeri 5 Mataram. The research sample used class XI 3 as many as 32 people as the experimental class and class XI 2 as many as 32 people as the control class. The experimental class was given treatment using a problem-based learning model assisted by PhET media and the control class used a conventional model. The test instrument used 5 descriptive questions to measure critical thinking skills and 6 questions to measure students' physics learning outcomes. The hypothesis test used in this study was the manova test. The results of the hypothesis test showed a significance value of 0.007 less than 0.05, so H_0 was rejected and H_a was accepted. Based on these results, it was concluded that there was an effect of the problem-based learning model assisted by PhET media on critical thinking skills and physics learning outcomes of high school students.